ANALYSIS OF FORBIDDEN PHARMACEUTICAL COMPOUINDS IN ANTIRHEUMATIC JAMU - Mustarichie, Resmi; Ramdhani, Danni; Indriyati, Wiwiek (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:To determine forbidden (by law) pharmaceutical compounds in antirheumatic jamu.) Methods: Analysis of forbidden pharmaceutical ingredients into jamu was carried out by using the color reaction, thin layer chromatography and densitometry. Color reactions included organoleptic, solubility test and the color reaction, TLC using a stationary phase of silica gel GF 254 and a mobile phase of chloroform; acetone (80:20) was then measured with a densitometer. Results: Found from 7 herbal anti-rheumatic known in the market, three of which were synthetic compounds containing paracetamol and dexamethasone additions on one of them. Conclusion: There was a synthetic drug that was added to the herbal medicine namely jamu sold in the community The obtained results suggest that the authorities more intensively to monitor the manufacture and distribution of jamu and herbal medicines Keywords: AntirheumaticJamu, herbal medicine, TLC, Densitometer, paracetamol, dexamethasone